EARLY DETECTION AND TREATMENT: AN EXAMINATION OF PRODROMAL SYMPTOMS OF POST OPERATIVE DELIRIUMIN ELDERLY PATIENTS - MATSUURA, JUMPEI (International Journal of Clinical and Biomedical Research, 2015)
Introduction: The development of postoperative delirium is a mental disorder common among those aged 70 and over in the wake of the surgery. The impact of postoperative delirium can be severe and result in withdrawal and deterioration in patients quality of life. The purpose of this study was to identity the prodromal symptoms perceived by veteran nurses to reflect onset of postoperative delirium among elderly patients in Japan. Methods: Participants A total of 300 nurses, each with over five years of nursing experience and over three years of clinical nursing experience on surgical wards, participated in this research. Consent and investigative cooperation was obtained from the nursing director of each hospital who was then sent copies of the questionnaire. Each director was requested to distribute the questionnaires among nurses in the surgical wards Participants. That met the inclusion criteria of this study. Questionnaires were returned by post in accordance with a three-week deadline. Results: The following items were to be most characteristic of postoperative delirium onset: "Has been refrain", "patient’s mood is dark", "patient complains of wound pain", "patient refuses to roll over", "patient complains of urgency", patient experiences a constant urge to have a bowel movement, the wrong time, patient refuses to adhere to their diet, and patient is unable to effectively use the nurses call. Conclusions: The results of this research revealed that prodromal symptoms identified by clinical nurses can be categorized into six distinct areas: behavior, confusion, negative symptoms, sleep, delusion, and excretion. KEYWORDS: Postoperative Delirium; Prodromal Symptoms; Early Detection; Questionnaires; Japan.